A research on HR sustainability practices in a retail company - De Asis, Paula Nicola S. (Animo Repository, 2022)
This paper analyzes the current HR practices of one of the leading grocery retailers in the Philippines and critical issues affecting the company. To determine this, the researchers collected data via qualitative surveys amongst 40 employees of one of the leading grocery retailers in the Philippines. To validate the data, the researchers did an in-depth interview among three employees and did non-participant observation in the retailer's workplace. The study identified issues that affect HR practices in the retail industry. The problems identified are the following: weak accountability, working beyond the scope of work, frequent changes in the company directed by upper management, unclear career paths, functioning for a higher role but not being adequately compensated, employees working on skeletal schedules, and long working hours due to heavy workload. The problems identified affected the morale of employees. The researchers proposed a new model of sustainable human resources fit for the grocery retail industry addressing the issues found in the study. This study emphasizes the importance of keeping employees engaged through sustainable HR practices. Grocery retail organizations can remain sustainable and profitable if their employees are well engaged and well-motivated.